Report from the third international consensus meeting to harmonise core outcome measures for atopic eczema/dermatitis clinical trials (HOME). (1st December 2014) - Chalmers, J.R.; Schmitt, J.; Apfelbacher, C.; Dohil, M.; Eichenfield, L.F.; Simpson, E.L.; Singh, J.; Spuls, P.; Thomas, K.S.; Admani, S.; Aoki, V.; Ardeleanu, M.; et al.
Summary: This report provides a summary of the third meeting of the Harmonising Outcome Measures for Eczema (HOME) initiative held in San Diego, CA, U.S.A., 6–7 April 2013 (HOME III). The meeting addressed the four domains that had previously been agreed should be measured in every eczema clinical trial: clinical signs, patient‐reported symptoms, long‐term control and quality of life. Formal presentations and nominal group techniques were used at this working meeting, attended by 56 voting participants (31 of whom were dermatologists). Significant progress was made on the domain of clinical signs. Without reference to any named scales, it was agreed that the intensity and extent of erythema, excoriation, oedema/papulation and lichenification should be included in the core outcome measure for the scale to have content validity. The group then discussed a systematic review of all scales measuring the clinical signs of eczema and their measurement properties, followed by a consensus vote on which scale to recommend for inclusion in the core outcome set. Research into the remaining three domains was presented, followed by discussions. The symptoms group and quality of life groups need to systematically identify all available tools and rate the quality of the tools. A definition of long‐term control is needed before progress can be made towards recommending a core outcome measure.